Struktura a antistruktura: rituál v pojetí Victora Turnera II = Structure and antistructure : Victor Turner's theory of ritual - Chlup, Radek (Religio, 2005)
The article gives a survey of Victor Turner's theory of ritual, summarizing its most important points and offering a critical appreciation of them. The first part deals with Turner's early conceptions as sketched in his Ndembu studies of the 1950s-60s. Building up on the new dynamic approach introduced into British anthropology of the 1950s by E. Leach and M. Gluckman, Turner abandoned the static structural model of society, as developed by A. R. Radcliffe-Brown, and focused on the dynamic aspect of social relations, seeing society as a drama in constant flow. Ritual is no longer conceived of as an instrument of stability and conservatism, but rather as an institutional framework enabling social change without letting social relations dissolve altogether. It is an arena in which all the conflicting facets of social life are confronted and have a chance to come to terms. This function of ritual is best seen in the nature of ritual symbols and their ability to connect various poles of meaning, thus mediating between ideal norms of the community and the often adverse individual ambitions of its members. The article then proceeds to deal with the best known. -- The article then proceeds to deal with the best known aspect of Turner's theory, his concepts of liminality and communitas as presented in The Ritual Process. It was particularly the notion of communitas that was innovative but that could also be criticized in many respects, Turner's own language being frequently imprecise and misleading. It is demonstrated what impact the concepts of liminality and communitas had on Turner's overall theory of ritual. Turner came to stress that all rituals worthy of the name must have something liminal in them, confronting structure with antistructure. No doubt this is a controversial claim and its pros and cons are analysed thoroughly. -- The last part of the article attempts to bring out Turner's importance for the study of religions. It is shown that his concept of liminality makes it possible to distinguish between religious and secular ritual in an interesting manner. At the very end it is emphasized that Turner offers a way of studying religion which is non-reductive and yet avoids theologizing and is firmly rooted in human social experience.